Effect of application of different fertilizers on shortening time of Sour orange (Citrus aurantium) seedlings to attain optimal budding stage - Mahmoud, Husameldin; Mohammed, Mayada; Alturki, Saleh; Emam, Abda; Yagoub, Samia (Edelweiss Applied Science and Technology, 2025)
The study was conducted to investigate the effects of different fertilizer applications on the growth of sour orange seedlings. The fertilizers tested included: (T1) fertigation with nitrogen, (T2) micronutrients alone, (T3) foliar application of amino acids combined with micronutrients, (T4) NPK plus trace elements (TE), (T5) NPK plus TE and magnesium (Mg), and (T0) as the control. The results demonstrated that the T3 treatment, which involved foliar application of amino acids combined with micronutrients, was superior in all vegetative characteristics. These characteristics included the number of leaves, stem diameter, length of the woody part of the stem, seedling height, number of new branches, total chlorophyll content, and stem girth. Additionally, T3 significantly shortened the period required to reach a suitable stem diameter for budding, achieving this in just 10 months (300 days). In comparison, the fertigation with nitrogen (T1) and the control (T0) treatments yielded the lowest values across all growth parameters. The foliar application of amino acids combined with micronutrients (T3) is recommended for optimal vegetative growth and faster development, enabling seedlings to attain the ideal stem diameter for budding within 10 months, which offers economic benefits. Conversely, nitrogen fertigation (T1) and the control (T0) showed poor growth performance and are not recommended for promoting seedling development.